Development Of Maritime Culture In Supporting Optimization Of Blue Economy Potential In West Kalimantan - Chairil Effendy; Muhammad Rafi Darajati; Annisa Dina Amalia (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
In this research, marine and fisheries development in West Kalimantan is directed at optimizing the management and sustainable use of natural resources, increasing fisheries productivity and production, expanding employment opportunities, supporting increased non-oil and gas exports and increasing consumption of fishery products. This data was collected through literature study and complemented by field observations and semi-structured interviews with groups of fishermen in Kampung Nelayan Kakap, Kubu Raya, West Kalimantan and related government agencies in West Kalimantan. By using the snowball sampling technique as an interview sample, the research results show that the majority of people's livelihoods in Fisherman's Village rely on catching fish, shrimp and crabs by fishermen using small traditional boats. The decreasing number of fish catches is also a problem faced by local fishermen, even though selling prices have increased in line with increasing demand for fishery products. The results of the interpretation are an effort to optimize maritime culture in the form of life behavior and human procedures as a nation's community towards the sea and the utilization of all the potential maritime wealth that exists in, on and around the sea to meet the living needs of society and the current economy of a country. present and future by exploring and developing ideas in the form of knowledge, social norm systems and the technology that supports them.